A Novel Oral Antiviral Drug for Covid-19. Can It Make a Difference? - Tahir, Moizza (Pakistan Armed Forces Medical Journal, 2023)
Countries across the world are striving to vaccinate their citizens against the virus that brings about COVID-19. Not only developed countries but also developing ones have had success in vaccinating a huge number of people. Advance and improved treatments are still required to reduce hospitalizations and deaths. They also aid in the prevention of virus propagation. It is important to recognize that, despite being vaccinated, there is still a need for alternative and more effective COVID treatment options. In the quest to create a solution for battling COVID-19, antiviral medicine was developed. The good thing about this solution is that it can be taken orally rather than intravenously which can be provided outside of a hospital setting before COVID-19 has progressed to a critical level.